The Upper Cretaceous dimorphic pachydiscid ammonite Menuites in the Western Interior of the United States - Cobban, W; Kennedy, W (1993)
Highly dimorphic pachydiscid ammonites are fairly abundant in Montana, South Dakota, Wyoming, and Colorado, and a few specimens are known from Utah and New Mexico. Two chronologic species are recognized, each represented by small adults (microconchs) and large adults (macroconchs). Microconchs have been assigned to Menuites Spath, 1922, whereas macroconchs have usually been assigned to Anapachydiscus Yabe and Shimizu, 1926. Both forms are considered Menuites in the present report. -from Authors